Raising market awareness - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The National Beekeepers? Association in The Gambia uses a variety of methods to promote its honey products. These include information sheets, advertisements in newspapers and on the radio, and an outdoor display table where customers can come to try different honey types.